Adaptive Gen-AI Guidance in Virtual Reality : A Multimodal Exploration of Engagement in Neapolitan Pizza-Making - Lau, Ka Hei Carrie; Sen, Sema; Stark, Philipp; Bozkir, Efe; Kasneci, Enkelejda (27th International Conference on Multimodal Interaction, ICMI 2025, Canberra, Australia, 2025-10-13 - 2025-10-17, 2025)
Virtual reality (VR) offers promising opportunities for procedural learning, particularly in preserving intangible cultural heritage. Advances in generative artificial intelligence (Gen-AI) further enrich these experiences by enabling adaptive learning pathways. However, evaluating such adaptive systems using traditional temporal metrics remains challenging due to the inherent variability in Gen-AI response times. To address this, our study employs multimodal behavioural metrics, including visual attention, physical exploratory behaviour, and verbal interaction, to assess user engagement in an adaptive VR environment. In a controlled experiment with (n = 54) participants, we compared three levels of adaptivity (high, moderate, and non-adaptive baseline) within a Neapolitan pizza-making VR experience. Results show that moderate adaptivity optimally enhances user engagement, significantly reducing unnecessary exploratory behaviour and increasing focused visual attention on the AI avatar. Our findings suggest that a balanced level of adaptive AI provides the most effective user support, offering practical design recommendations for future adaptive educational technologies.
Publisher Copyright: © 2025 Copyright held by the owner/author(s).
Keywords: generative artificial intelligence; intangible culture heritage; virtual reality